Analyzing The Successful Implementation of General Procurement Information System (Sirup) Using The Delone and Mclean Model in Muna Regency, Southeast Sulawesi - Nurnila Nurnila; Etin Indrayani; Ruth Roselin Ernawaty Nainggolan; Sity Daud (Jurnal Teknologi dan Komunikasi Pemerintahan, 2025)
The Muna District Government has also applied SIRUP to ease the announcement of procurement of goods and services. But the general success of this information system in the work units of Muna Regency has not been much studied. So that in this study, it will be tested the success of the information system on the General Procurement Plan in Muna Regency based on Delone and McLean Model of the information system. The purpose of this study is to evaluate how well the information system worked in the work units of the regency's government. The evaluation applies the Delone and McLean model with six dimensions: system quality, service quality, information quality, user satisfaction, user usage, and net benefit. This research uses quantitative approach with descriptive and statistical analysis methods. There is only one finding that system quality significantly influences usage. Meanwhile, system quality, information, and service significantly affect user satisfaction. Therefore, the conclusion is that the government needs to increase innovation and improve the management of service and system quality to enhance user engagement and raise awareness of the SIRUP Application, thereby increasing user satisfaction with it.   Keywords: Delone and McLean, SIRUP Application, Success Analysis, Procurement Announcement, Information System.